2018
DOI: 10.4152/pea.201806403
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine Duality Effect on the Corrosion Inhibition and Acceleration of 3003 Aluminium Alloy in a 2% NaCl Solution

Abstract: Cysteine's action on 3003 aluminum alloy dissolution in a 2% NaCl solution, at different pH values, has been investigated. Weight-loss measurements, potentiodynamic polarization and electrochemical impedance at OCP were performed. The surface morphology was analyzed by SEM. The main results showed that the alloy underwent severe corrosion at 2 and 11 pH values, as compared to at 5 and 8 pH values. Furthermore, a duality effect of cysteine was noted, as it acted as a corrosion inhibitor or accelerator, dependin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…In the acidic media, similar impedance spectra have been reported in the corrosion literature for aluminum and its alloys [23,25,26,[28][29][30][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64]. The addition of the OMW does not affect the shape of the loops, indicating that no change in the corrosion mechanism of AA3003 alloy has occurred [65]. The impedance data are simulated by using the equivalent circuit illustrated in Figure 3 [66].…”
Section: Electrochemical Impedance Spectroscopy Results Thementioning
confidence: 75%
See 1 more Smart Citation
“…In the acidic media, similar impedance spectra have been reported in the corrosion literature for aluminum and its alloys [23,25,26,[28][29][30][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64]. The addition of the OMW does not affect the shape of the loops, indicating that no change in the corrosion mechanism of AA3003 alloy has occurred [65]. The impedance data are simulated by using the equivalent circuit illustrated in Figure 3 [66].…”
Section: Electrochemical Impedance Spectroscopy Results Thementioning
confidence: 75%
“…Accordingly, the calculated impedance parameters are given in Table 4. The inhibitory efficiency derived from the charge transfer resistance is obtained by the following relationship [49,58,65]:…”
Section: Electrochemical Impedance Spectroscopy Results Thementioning
confidence: 99%
“…In the present chapter, we interesting in the organic inhibitor category, which its protection ability is related to its adsorption onto the metal surface via electrostatic attraction or/and chemical bond formation, leading to the formation of a protective layer resulting in corrosion mitigation [8]. It is well known that the adsorption process of these compounds occurs via their electron-donator sites like heteroatoms (N, O, S and P) and multiple bonds (π-bonds) and aromatic rings as well.…”
Section: Introductionmentioning
confidence: 99%
“…13 According to the available literature, cysteine and methionine amino acids have been studied extensively. [14][15][16][17][18][19][20] Nevertheless, studies on the application of this class of molecules for tin metal are still limited. Among the existing physiological amino acids, proline (Pro, Fig.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it was reported that the pH of the solution plays a decisive role, in which an inhibitor can be effective at certain pH values, while being nominal at other values. 16 Specically, a variation in pH leads to substantial modications in the inhibition system, especially the protonation state of the inhibitor molecule and the chemical composition of the metal surface. This means that the inhibitor/metal interactions will be affected by this variation, and subsequently, the observed inhibition behavior will also be modied.…”
Section: Introductionmentioning
confidence: 99%